The conception of a rubric to evaluate educational portals on the web - Bottentuit Junior, João Batista (2008)
As the ease of Internet access and the quantity of available information increases, it also increases the apprehension of the educators regarding the issues of credibility of the available contents on the sites, as well as the quality of its technical functionalities. Educational portals are developments of conventional sites. That is, they are resources and information sources concentrated on the same site, becoming interesting to a rather diversified public and having major potentialities to complement, at several levels, the teaching and learning processes. However, for such an important mission to be accomplished it is key that, in the development and maintenance process of an educational website, a series of requisites are to be accomplished in order to guarantee the quality of the available information, as well as the usability. As we were thinking on these issues we developed an analysis and evaluation grid for educational portals. This was made through the comparison of a set of criteria, which we have considered essential to guarantee the graphical quality and usability of an educational portal.